Effect of hyperbaric oxygen therapy on thiol/disulfide homeostasis in patients with idiopathic sudden sensorineural hearing loss - Cigdem Damla Cetinkaya; Mehmet Ali Eryilmaz; Salim Neselioglu; Ruhusen Kutlu; Abdullah Arslan; İbrahim Solak; Ozcan Erel; Betul Kozanhan (SERNEV, 2018)
Introduction: Idiopathic sudden sensorineural hearing loss (ISSNHL) isan otologic emergency that can lead to loss of function in one of the mostimportant human senses. Recently, hyperbaric oxygen therapy (HBOT) has gainedpopularity with pharmacotherapy in ISSNHL. This study aimed to determinechanges induced in thiol/disulfide homeostasis (TDH, a new biomarker ofsystemic oxidative stress) by pharmacotherapy and HBOT in patients with ISSNHL.Methods: This prospectivestudy analyzed the albumin, total thiol, native thiol, and disulfide levels anddisulfide-native thiol, disulfide-total thiol, and native thiol-total thiolratios before and after HBOT with standardizing pharmacotherapy using a newcolorimetric method in patientswith ISSNHL.Results: 41 patients withISSNHL including 14 (34.1%) women and 27 (65.9%) men participated in the study.The mean age of the patients was 48.02 ± 13.10 years. Of them, 24 (58.5%) hadhearing loss in the right ear and 17 (41.5%) had hearing loss in the left ear.There was a statistically significant decrease in the albumin (p lt;0.001),total thiol (p lt;0.001), native thiol (p lt;0.001), and disulfide (p lt;0.001)levels after treatment compared to baseline. There was no statisticallysignificant difference in the disulfide-native thiol (p=0.148), disulfide-totalthiol (p=0.172), and native thiol-total thiol (p=0.169) ratios after treatmentcompared to baseline.Conclusion: Consequently,this study demonstrated that the thiol-disulphide balance tended to shifttowards the oxidative side after HBOT and pharmacotherapy compared to baseline in patients with ISSNHL andthat patients with high oxidation level after treatment had better treatmentresponse.